Entrepreneurship in advanced and developing countries: A microeconomic perspective - Marco Vivarelli (Institute for the Study of Labor (IZA), 2012)
The purpose of this paper is to provide a contribution to the identification of the role of entrepreneurship in economic growth by mapping out: 1) alternative ways of looking at entrepreneurship, distinguishing 'creative destruction' from simple 'turbulence'; 2) the different microeconomic determinants of new firm formation, distinguishing 'progressive' from 'regressive' drivers; 3) the relationship between ex-ante characteristics (of the founder) and post-entry performance (of the new firm); and 4) the possible scope for an economic policy aimed at maximizing the impact of entrepreneurship on economic growth. Where possible and appropriate, throughout the paper particular attention is devoted to the specific features characterizing entrepreneurship in developing countries.
urn:nbn:de:101:1-201208096318
Keywords: L26; O12; 330; entrepreneurship; new firm; innovation; development; Unternehmer; Unternehmensgründung; Wirtschaftswachstum; Entwicklung; Entwicklungsländer; Industriestaaten